Pengenalan akan Allah dalam Pengalaman Hidup Kaum Muda Katolik - Juli Antonius Sihotang (Perkumpulan Perguruan Tinggi Agama Katolik Indonesia, 2021)
The purpose of this research is to deepen the knowledge of God in the experience of human life every day so that His paradoxical existence does not stop humans from getting to know Him more. This research has four problem formulations. First, how do young Catholics understand hope? Second, how do young Catholics understand the faith? Third, how do young Catholics experience God when faced with life's difficulties and sufferings? Fourth, what makes young Catholics hope and believe in God until now? This study uses a descriptive research method with a qualitative approach. The informants of this study were 13 young Catholics who had various educational and work backgrounds, places of residence, and ages. The data collection techniques used were interviews via Facebook and Instagram and sharing google forms questions via email. The results of this study indicate that hope is understood as the gripping force of human life. While faith is the basis of hope and trust in God which enables a person to experience His presence and help in dealing with the difficulties and sufferings of life. Thus, young Catholics hope and believe in God in life, even though the reality is not always easy. This study found that knowing God will only be experienced if a person has a good and deep understanding of hope and faith in his life's pilgrimage in this world.